Impairment of K‐Ras signaling networks and increased efficacy of epidermal growth factor receptor inhibitors by a novel synthetic miR‐143. Issue 5 (14th April 2018) - Akao, Yukihiro; Kumazaki, Minami; Shinohara, Haruka; Sugito, Nobuhiko; Kuranaga, Yuki; Tsujino, Takuya; Yoshikawa, Yuki; Kitade, Yukio
Abstract : Despite considerable research on K‐Ras inhibitors, none had been established until now. We synthesized nuclease‐resistant synthetic miR‐143 (miR‐143#12), which strongly silenced K‐Ras, its effector signal molecules AKT and ERK, and the K‐Ras activator Sos1. We examined the anti‐proliferative effect of miR‐143#12 and the mechanism in human colon cancer DLD‐1 cell (G13D) and other cell types harboring K‐Ras mutations. Cell growth was markedly suppressed in a concentration‐dependent manner by miR‐143#12 (IC50 : 1.32 nmol L −1 ) with a decrease in the K‐Ras mRNA level. Interestingly, this mRNA level was also downregulated by either a PI3K/AKT or MEK inhibitor, which indicates a positive circuit of K‐Ras mRNA expression. MiR‐143#12 silenced cytoplasmic K‐Ras mRNA expression and impaired the positive circuit by directly targeting AKT and ERK mRNA. Combination treatment with miR‐143#12 and a low‐dose EGFR inhibitor induced a synergistic inhibition of growth with a marked inactivation of both PI3K/AKT and MAPK/ERK signaling pathways. However, silencing K‐Ras by siR‐KRas instead of miR‐143#12 did not induce this synergism through the combined treatment with the EGFR inhibitor. Thus, miR‐143#12 perturbed the K‐Ras expression system and K‐Ras activation by silencing Sos1 and, resultantly, restored the efficacy of the EGFR inhibitors. The in vivo results also supported those of the in vitro experiments. The extremely potent miR‐143#12 enabled us to understand K‐Ras signaling networks and shut them down by combination treatment with this miRNA and EGFR inhibitor in K‐Ras‐driven colon cancer cell lines. Abstract : The extremely potent miR‐143#12 enabled us to well understand K‐Ras signaling networks and shut them down by combination treatment with this miRNA and EGFR inhibitor in K‐Ras‐driven colon cancer cell lines.